Associated factors, assessment, management, and outcomes of patients who present to the emergency department for acute exacerbation of chronic obstructive pulmonary disease: A scoping review. (March 2022) - Phillips, Tania M.; Moloney, Clint; Sneath, Emily; Beccaria, Gavin; Issac, Hancy; Mullens, Amy B.; Gow, Jeff; Rana, Rezwanul; King, Alex
Abstract: Objective: The purpose of the scoping review was to examine the extant literature for factors contributing to presentations of Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) to Emergency Departments (ED). Methods: The review followed Arksey and O'Malley, and Levac's frameworks supplemented with the PRISMA-ScR checklist. We searched Cochrane Library, CINAHL, JBI, and PubMed from January 1, 2008 to March 23, 2020 for inclusions. We included studies reporting ED presentations for AECOPD among adults (≥18 years). The investigation included: pre-hospital factors; ED-related assessment, management and referral practices; holistic management (i.e., interdisciplinary); patient outcomes, admission/discharge status, and readmission. Results: Forty-four studies were included. Environmental factors (e.g., air pollution, seasonal change); social determinants (e.g., poor literacy, ethnicity); and physical health (e.g., comorbidities, obesity, poor exercise capacity) contributed to ED presentation/re-presentation, and admission to hospital. Cigarette smoking was associated with hospital admission. Mortality was associated with longer-term oxygen therapy, poor exercise capacity, age, and loss of consciousness. Compliance with clinical guideline recommendations were generally low or mixed. Further, there was a lack of appropriate referral practices upon discharge. Conclusions: While there is considerable literature on factors contributing to AECOPD admission more research is required that investigates the impact that inter-professional care models can have on the discharge planning cycles for patients with COPD who are regular presenters to an ED. Highlights: Compliance with clinical guideline recommendations were generally low or mixed. Lack of appropriate referral practices upon discharge from ED. Lack of appropriate patient self-management education. More research needed on inter-professional models of care and discharge planning.